KONSTITUSI SEBAGAI TOLAK UKUR EKSISTENSI NEGARA HUKUM MODERN - Sari, Indah (JURNAL ILMIAH HUKUM DIRGANTARA, 2018)
Constitution is a basic and principle regulation which govern a state through a written law (like Undang-undang Dasar) or unwritten law (like convention). Every citizen and every state officer should conform to the constitution as a guidance of their act in a country. A constitution reflects a modern and supreme state of law that measure some acknowledgment and protection of human rights, in which freedom, equality, transparency, justice and control of power principles should be delivered. We can administer, by the secondition, a welfare state that would deliver prosperity and order for every citizen. Keywords : constitution, state, state of law, modern state of law.